Dolphin echolocation algorithm for small-signal stability analysis of DFIG-based wind power system. (17th December 2021) - Kashiv, Ashutosh; Verma, H.K.
In this paper stability examination of a doubly-fed induction generator (DFIG) wind turbine system has been done. DFIG wind turbine system is modelled using the state-space method. The main aim of the paper is to examine the behaviour of the DFIG at the various speeds of the rotor. This paper mentions the application of the proportional-integral controller optimised by dolphin echolocation optimisation algorithm (DEOA) to get efficient as well as stable operation of the DFIG system. For this purpose, damping ratios and eigenvalues are taken as a result. The simulation results were compared with those obtained using the particle swarm optimisation (PSO) approach for the proposed DFIG model. Simulation data show that the DEOA-PI controller works well to limit the transient in voltage and current response for the DFIG model under consideration.